THE IMPORTANCE OF ORGANIZATIONS PERFORMANCE ON ORGANIZATIONAL GROWTH - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Accurate and appropriate measurement of performance is a critical element in entrepreneurship research (Aktan, Bulut, 2008). According to Achemfuor,(2012), a well-organised system of performance measurement may be the single most powerful mechanism at management’s disposal to enhance the probability of successful strategy implementation. In many of the studies in the field of strategic entrepreneurship, firm performance is defined as a dependent variable and the entrepreneurship activity of the firm is considered an independent variable. There is strong agreement among the researchers that the results of successful entrepreneurial activities positively correlate with the improvement of a company’s performance (Fairoz, Hirobumi& Tanaka, 2010). Measuring absolute firm performance is very difficult, because the concept is complex and multi-dimensional. Researchers suggest that multiple performance indicators should be used to measure this complex construct (Farrington, Matchaba, 2011). The predictable approach to firm’s performance has been to consider financial performance (Frank, Kessler & Fink, 2010). Another approach to organisational performance is to use measurement against purpose, using perceptual measures of company performance (Fatoki, 2012).